The Experience of Students in Medical Sciences In Their Studies Abroad In Recent Years - Ali Akbar Haghdoost; Ali Akbar Haghdoost; Mahmood Reza Dehghani; Seyed Amin Ayatollahimousavi; Yasaman Nafisi; Elham Pourkhandani; Pardis Sasani; Azam Bazrafshan; Ali Pourkhandani; Elham Talebian; Rahele Zareshahi (Kerman University of Medical Sciences, 2011)
Background and Objective: Scholarship is of such a great importance that even the developed countries pay special attention to it while in developing countries it has been left unattended and there is no appropriate management to benefit from the its advantages For this scholarship has to be considered more seriously in the planning system of the country in order to achieve the highest yield beside all expenses Methods: Using registered documents as one of the best information sources 366 students awarded scholarship between19972003 were enrolled into the study Students personal information at the time of going abroad scholarship granted university local university and students major and duration of study were considered as useful information and excluded carefully from electronic and paper documents under the cooperation of the scholarship office of Ministry of Health and Medical Education Results: Most of the students were studying in European countries (697%) and Australian and Oceania universities (126%) The average duration of study was (±046) 407 years for PhD and (± 054)512 years for clinical specialty candidates showing a significant difference between the two groups (P‹ 0001) However the noticeable point is that nonreturning rate has been more than average for students who have received scholarship from those universities and also the ministry while scholarship holders from level three universities were successful in science generating Conclusion: The highest number of awarded scholarships belonged to the large universities in the country and based on the available information it is difficult to judge whether scholarship awarding has been distributed fairly among universities or not